2020
DOI: 10.1109/access.2020.3040733
|View full text |Cite
|
Sign up to set email alerts
|

Dual Deep Neural Network Based Adaptive Filter for Estimating Absolute Longitudinal Speed of Vehicles

Abstract: This study employs a dual deep neural network (D-DNN) to accurately estimate the absolute longitudinal speed of a vehicle. Accuracy in speed estimation is crucial for vehicle safety, because longitudinal speed is a common parameter employed as a state variable in active safety systems such as antilock braking system and traction control system. In this study, DNNs are applied to determine the gain of an adaptive filter to estimate vehicle speed. The used data consists of longitudinal acceleration, wheel speed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In addition to traditional filtering algorithms, other researchers have explored integrating deep learning techniques to estimate vehicle state parameters efficiently. Kim J et al [18] suggested an adaptive filter that utilizes dual deep neural networks for vehicle state estimation. This method utilizes deep learning capabilities to enhance the adaptive filtering process, offering a more accurate and robust alternative in dynamic and complex environments, thus demonstrating the potential application of deep learning in vehicle state estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to traditional filtering algorithms, other researchers have explored integrating deep learning techniques to estimate vehicle state parameters efficiently. Kim J et al [18] suggested an adaptive filter that utilizes dual deep neural networks for vehicle state estimation. This method utilizes deep learning capabilities to enhance the adaptive filtering process, offering a more accurate and robust alternative in dynamic and complex environments, thus demonstrating the potential application of deep learning in vehicle state estimation.…”
Section: Introductionmentioning
confidence: 99%